Obstacle Detection Display for Visually Impaired: Coding of Direction, Distance, and Height on a Vibrotactile Waist Band - van Erp, Jan B. F.; Kroon, Liselotte C. M.; Mioch, Tina; Paul, Katja I. (Frontiers in ICT, 2017)
Electronic Travel Aids (ETAs) can potentially increase the safety and comfort of blind users by detecting and displaying obstacles outside the range of the white cane. In a series of experiments we aim to balance the amount of information displayed and the comprehensibility of the information taking into account the risk of information overload. In Experiment 1 we investigate perception of compound signals displayed on a tactile vest while walking. The results confirm that the threat of information overload is clear and present. Tactile coding parameters that are sufficiently discriminable in isolation may not be so in compound signals and while walking and using the white cane. Horizontal tactor location is a strong coding parameter and temporal pattern is the preferred secondary coding parameter. Vertical location is also possible as coding parameter but it requires additional tactors and makes the display hardware more complex and expensive and less user friendly. In Experiment 2 we investigate how we can off-load the tactile modality by mitigating part of the information to an auditory display. Off-loading the tactile modality through auditory presentation is possible, but this is off-loading is limited and may result in a new threat of auditory overload. In addition, taxing the auditory channel may in turn interfere with other auditory cues from the environment. In Experiment 3 we off-load the tactile sense by reducing the amount of displayed information using several filter rules The resulting design was evaluated in Experiment 4 with visually impaired users. Although they acknowledge the potential of the display, the added of the ETA as a whole also depends on its sensor and object recognition capabilities. We recommend to use not more than two coding parameters in a tactile compound message and apply filter rules to reduce the amount of obstacles to be displayed in an obstacle avoidance ETA.